2007
DOI: 10.1190/1.2732549
|View full text |Cite
|
Sign up to set email alerts
|

3D ray tracing using a modified shortest-path method

Abstract: We present an accurate 3D ray-tracing algorithm based on a modified (more flexible and economical) shortest-path method (SPM). Unlike the regular SPM in the 3D case, which uses only primary nodes at the corners of each cell and whose accuracy depends on actual cell size, the new method can work with much larger cell sizes by introducing secondary nodes along all bounding surfaces of the cell. This increases the ray angular coverage and permits detailed specification of the velocity field. The modified SPM simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 25 publications
3
52
0
Order By: Relevance
“…Secondary nodes are introduced along the cell surfaces between the primary nodes to improve ray coverage (for secondary node definition; BAI et al, 2007); and 2. A one step wavefront expanding algorithm is used, not a forward star scheme (MOSER, 1991;KLIMEŠ and KVASNIČ KA, 1994), to propagate the wavefront outward efficiently.…”
Section: Summary Of the Multistage Irregular Shortestpath Ray Schemementioning
confidence: 99%
See 2 more Smart Citations
“…Secondary nodes are introduced along the cell surfaces between the primary nodes to improve ray coverage (for secondary node definition; BAI et al, 2007); and 2. A one step wavefront expanding algorithm is used, not a forward star scheme (MOSER, 1991;KLIMEŠ and KVASNIČ KA, 1994), to propagate the wavefront outward efficiently.…”
Section: Summary Of the Multistage Irregular Shortestpath Ray Schemementioning
confidence: 99%
“…As a result, the irregular shortest-path ray-tracing algorithm is one order of magnitude faster in CPU time than the traditional shortest-path ray tracing scheme (BAI et al, 2007). The multistage computational scheme means that the velocity model is divided into several layers (or computational domains), corresponding to the major velocity discontinuities.…”
Section: Summary Of the Multistage Irregular Shortestpath Ray Schemementioning
confidence: 99%
See 1 more Smart Citation
“…The above definition of the velocity distribution across the cell allows us to handle arbitrary media with only a slightly increased effort in the computations to trace any ray paths, irrespective of where the sources and receivers are located. BAI et al (2004) showed that the revised 'irregular' shortest path method has a maximum relative error in 3-D situations given by:…”
Section: Velocity Function Across the Cellmentioning
confidence: 99%
“…BAI et al (2004) analyzed the relative performance between the 'irregular' and 'regular' shortest path approaches at a specified accuracy, and established the CPU ratio in terms of the level of forward star n FS ('regular' approach) and the number of nodes (n) per cell boundary ('irregular' approach) as:…”
Section: Algorithm Accuracy and Computational Efficiencymentioning
confidence: 99%